2018
DOI: 10.1080/1744666x.2018.1440206
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced myalgia and myositis: an update on pathogenesis and clinical recommendations

Abstract: Introduction Musculoskeletal manifestations are well-recognized side effects of treatment with statins. New advances in this field have appeared in recent years. This review focuses on the diagnosis of these conditions and their underlying pathogenesis, in particular immune-mediated necrotizing myopathy. Areas covered Clinical phenotypes including rhabdomyolysis, myalgia and/or mild hyperCKemia, self-limited toxin statin myopathy, and immune-mediated necrotizing myopathy are herein described. Therapeutic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 69 publications
2
128
0
7
Order By: Relevance
“…Statins inhibit hydroxymethylglutaryl coenzyme reductase, which is important for mevalonate production, a precursor to cholesterol synthesis . Mevalonate is used to anchor guanosine triphosphatases, and if disrupted can affect cytoskeleton formation resulting in rhabdomyolysis.…”
Section: Pathology and Imaging Resultsmentioning
confidence: 99%
“…Statins inhibit hydroxymethylglutaryl coenzyme reductase, which is important for mevalonate production, a precursor to cholesterol synthesis . Mevalonate is used to anchor guanosine triphosphatases, and if disrupted can affect cytoskeleton formation resulting in rhabdomyolysis.…”
Section: Pathology and Imaging Resultsmentioning
confidence: 99%
“…These fully human monoclonal antibodies (e.g. evolucumab, alirocumab), which act against the proprotein convertase subtilisin/kexyn type 9, could be an alternative to statin therapy in severe cases of drug toxicity, such as rhabdomyolysis [1]. Clinical studies comparing statins versus statins + anti-PCSK9 found no differences in muscle and CPK side effects between the two groups [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide diffusion of statins, which have the undoubted merit of increasing the survival rate in patients affected by cardiovascular disease, particular attention should be paid to their side effects. The most common ones are toxic myopathies, affecting 2-20% of patients [1], that generally resolve after drug discontinuation. The risk of statin myopathy and creatine phosphokinase (CPK) increase is dose-dependent.…”
Section: Introduction Statinsmentioning
confidence: 99%
“…Statins are essential drugs in the treatment of dyslipidaemia, and thus in the prevention of cardiovascular diseases. Despite statins are generally safe, a variety of myopathies have been reported following treatment (Selva-O'Callaghan et al, 2018). In fact, 10.5% of patients on statin therapy may experience myalgia, which is the most common side effect (Bruckert, Hayem, Dejager, Yau, & Bégaud, 2005).…”
Section: Statin-induced Myopathymentioning
confidence: 99%